Indonesian Migrant Community Behavior and Awareness in Providing Education Rights for Children - Aththoillah, Muhammad Sabiq; Mahardhani, Ardhana Januar; Cahyono, Hadi; Majid, Ikhwanuddin Abdul (Didaktika Religia, 2024)
Migrant workers frequently face many problems and difficulties, such as not having official documents such as deeds, family cards, passports, and residence permits. The absence of these documents prevents migrant workers from enjoying their rights, such as the right to send their children to school and healthcare. This research aims to analyze the behavior of Indonesian migrant communities and their awareness of the need to provide education rights for children. The type of research used is qualitative with a descriptive approach. The subjects of this research are the Indonesian migrant community and the manager of the Sanggar Bimbingan Gombak Utara.  Data were collected through interviews, observation, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The results show that migrant workers show high responsibility for their children's education rights. Despite being faced with legal document constraints, migrant workers are proactive in finding solutions. The government’s initiative through the sanggar bimbingan shows its seriousness in fulfilling the right to education. The research findings show that, despite facing economic challenges, migrant workers still give high priority to their children’s education.